HUBUNGAN KOORDINASI MATA-KAKI DENGAN KEMAMPUAN SEPAK SILA PADA ATLET PERSATUAN SEPAKTAKRAW SELURUH INDONESIA (PSTI) KABUPATEN KAMPAR - Jufrianis '; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this research is whether there is a relationship of eye-foot coordination with ability sila kick. The goal is to find out how big the eye-foot coordination with ability sila kick whether singly or jointly. The technique of sampling performed with total sampling of 12 athlete of Persatuan Sepaktakraw Seluruh Indonesia (PSTI) Kampar Districk. This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of α = 0.05. Test of normality of variabels X, L0maks (0,112) < Ltabel (0,242), and testing normality of variabels Y, L0maks (0,234) < Ltabel (0,242) in other words at a confidence level of 95% of normal data and concluded the results showed: there is a significant relationship between eye and food coordination with ability sila kick, with correlation r= 0.653, where rhitung > rtabel or 0.653 > 0,602. and such relations are categorized strong . Thus, Ho rejected and Ha accepted. Key word:  relationship,  eye-foot coordination,  ability sila kick.